Association of a homozygous GCK missense mutation with mild diabetes. Issue 7 (14th June 2019) - Marucci, Antonella; Biagini, Tommaso; Di Paola, Rosa; Menzaghi, Claudia; Fini, Grazia; Castellana, Stefano; Cardinale, Giuliana Marcella; Mazza, Tommaso; Trischitta, Vincenzo
Abstract: Background: Homozygous inactivating GCK mutations have been repeatedly reported to cause severe hyperglycemia, presenting as permanent neonatal diabetes mellitus (PNDM). Conversely, only two cases of GCK homozygous mutations causing mild hyperglycemia have been so far described. We here report a novel GCK mutation (c.1116G>C, p.E372D), in a family with one homozygous member showing mild hyperglycemia. Methods: GCK mutational screening was carried out by Sanger sequencing. Computational analyses to investigate pathogenicity and molecular dynamics (MD) were performed for GCK‐E372D and for previously described homozygous mutations associated with mild ( n = 2) or severe ( n = 1) hyperglycemia, used as references. Results: Of four mildly hyperglycemic family‐members, three were heterozygous and one, diagnosed in the adulthood, was homozygous for GCK‐E372D. Two nondiabetic family members carried no mutations. Fasting glucose ( p = 0.016) and HbA1c ( p = 0.035) correlated with the number of mutated alleles (0–2). In‐silico predicted pathogenicity was not correlated with the four mutations' severity. At MD, GCK‐E372D conferred protein structure flexibility intermediate between mild and severe GCK mutations. Conclusions: We present the third case of homozygous GCK mutations associated with mild hyperglycemia, rather than PNDM. Our in‐silico analyses support previous evidences suggesting that protein stability plays a role in determining clinical severity of GCK mutations. Abstract : We report the third, so far described, homozygous GCK mutation causing mild hyperglycemia. Together with previous experimental data, our present finding strongly suggests a role of protein stability on GCK mutations clinical severity.